Impedance Probe Testing Prior to Pediatric Airway Reconstruction. (September 2014) - Hart, Catherine K.; de Alarcon, Alessandro; Tabangin, Meredith E.; Hamilton, Steven; Rutter, Michael J.; Pentiuk, Scott P.; Garza, Jose M.
Objective: This study aimed to determine if preoperative impedance testing changed management and if testing was associated with surgical outcome in patients undergoing airway reconstruction. Methods: Retrospective review of patients who had impedance testing prior to airway reconstruction at a tertiary pediatric hospital from January 2010 to September 2011. Charts were reviewed for demographics, medical/surgical history, impedance testing, and surgical outcomes. Results: Fifty-seven patients were included. Forty-seven (82%) were premature. Forty-seven (82%) had a primary diagnosis of subglottic stenosis. Twenty-six (45%) had prior airway surgery. Thirty-six (63%) had gastroesophageal reflux and 21 (36%) had undergone fundoplication. Patients without fundoplication had a median 46 total reflux, 7 proximal, and 14.5 acidic events compared to a median 5 total reflux, 0 proximal, and 0 acidic events in patients with fundoplication. Impedance testing changed management in 22% (8/36) of nonfundoplication patients and 9.5% (2/21) of fundoplication patients. In unadjusted analysis, fewer fundoplication patients had successful surgery compared to those without (33% vs 67%, P = .01). Prematurity, age at surgery, and previous airway surgery were also important predictors of surgical success. Conclusion: Fewer patients than anticipated had a change in management. Impedance testing was unlikely to change management in fundoplication patients. Patients with fundoplication were less likely to have a successful outcome, suggesting that factors other than reflux influence airway reconstruction outcomes.